2010
DOI: 10.1007/s10681-010-0184-1
|View full text |Cite|
|
Sign up to set email alerts
|

Population genetics of self-incompatibility and developing self-compatible genotypes in niger (Guizotia abyssinica)

Abstract: Niger (Guizotia abyssinica (L. f.) Cass.(Asteraceae) is a strictly self-incompatible crop species with a sporophytic self-incompatibility mechanism. This characteristic presents a number of difficulties in plant improvement programs. The objective of this study was to determine the number and distribution of S-alleles in Ethiopian niger populations and to identify and develop self-compatible genotypes with various associated advantages. Several aspects of self-incompatibility in niger were compared in selfand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…These findings are consistent with Riley and Belayneh (1989) when they reported that niger has a small degree of self-compatibility though the plants may not necessarily be truly selfcompatible. A previous study by Geleta and Bryngelsson (2010) found that niger is a strictly self-incompatible crop of sporophytic nature, though nine plants out of the 340 evaluated showed some degree of compatibility.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with Riley and Belayneh (1989) when they reported that niger has a small degree of self-compatibility though the plants may not necessarily be truly selfcompatible. A previous study by Geleta and Bryngelsson (2010) found that niger is a strictly self-incompatible crop of sporophytic nature, though nine plants out of the 340 evaluated showed some degree of compatibility.…”
Section: Discussionmentioning
confidence: 87%
“…The pollen–stigma reaction results in callose production (Takayama and Isogai, 2005). In dicots, self-incompatibility (SI) is mapped to a single genetic locus called the S-locus (Geleta and Bryngelsson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only a small proportion of genetic variance ( F st = 0.044) occurred among noug populations. Genetic exchange between different noug accessions is facilitated by the fact that the crop has a self‐incompatibility system and is obligately outcrossing (Geleta and Bryngelsson ). Crops with self‐incompatibility systems are known to be more challenging to improve through breeding, as it is difficult to keep lines of interest ‘true to type.’ If an interesting phenotype is discovered in a certain accession, there is a high risk that the phenotype of interest will no longer be present in the next generation, as maintenance of the genetic identity of the line through selfing is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns at SI loci are similar to those at het/vic and FuHC. In G. abyssinica (niger), 97% of the SI locus variation was found within populations, and F ST values were very low (although statistically significant) (Geleta and Bryngelsson 2010). F ST values are significantly lower when compared to neutral loci, in all cases ( A. lyrata: Kamau et al 2007; A. halleri: Ruggiero et al 2008; B. cretica: Edh et al 2009; B. insularis: Glemin et al 2005).…”
Section: Discussionmentioning
confidence: 99%